Correction to: Virtual memory cells make a major contribution to the response of aged influenza-naïve mice to influenza virus infection - Kathleen G. Lanzer (Immunity & Ageing, 2018)
In the original publication of this article [1] there is an error in Fig. 3a as the labels “TM” and “VM” are in the wrong order for the last plot. The CD49d high cells should be “TM” and the CD49d low cells should be “VM”.